Resonant Raman scattering on carbon nanotubes covalently functionalized with lithium decyne - Müller, Matthias; Meinke, Reinhard; Maultzsch, Janina; Gebhardt, Benjamin; Hauke, Frank; Hirsch, Andreas; Thomsen, Christian (physica status solidi (b), 2010)
We present resonant Raman measurements on single-walled carbon nanotubes covalently functionalized with lithium decyne. We study the influence of the functional moieties on the optical transitions of the nanotubes. From the extracted resonance profiles of the radial breathing modes the chiral indices of the corresponding tubes are assigned. Slight red shifts of the optical transitions are observed, which implies only a little charge transfer due to the chemical reaction. The reaction shows a pronounced diameter dependence as previously observed for comparable reactions with different addends.Carbon nanotubes covalently functionalized with decyne moieties. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.